2020
DOI: 10.1177/1468087420934601
|View full text |Cite
|
Sign up to set email alerts
|

Autoignition characteristics of diesel spray under different injection pressures and cold start strategy for compression ignition engines

Abstract: Poor cold start performance is one of the main factors restricting the application range of compression ignition engines. Stable flame generation in the cylinder is the prerequisite for the successful start of the engine. In order to explore ways to improve the cold start ability of the compression ignition engine, the ignition characteristics of diesel sprays at different injection pressures were studied in a constant volume combustion chamber. A high-speed photography technique was used to obtain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…According to the study of Mohan et al [62], enhanced fuel atomization and lower HC, CO, and PM emissions could be achieved by increasing the injection pressure from diesel engines during cold start conditions. Through experiments in a constant volume combustion chamber (CVCC), Yang et al [63] demonstrated that injection pressure and flames can be successfully controlled with a slower start-up speed and a cool intake temperature.…”
Section: Injection Optimizationmentioning
confidence: 99%
“…According to the study of Mohan et al [62], enhanced fuel atomization and lower HC, CO, and PM emissions could be achieved by increasing the injection pressure from diesel engines during cold start conditions. Through experiments in a constant volume combustion chamber (CVCC), Yang et al [63] demonstrated that injection pressure and flames can be successfully controlled with a slower start-up speed and a cool intake temperature.…”
Section: Injection Optimizationmentioning
confidence: 99%
“…6 Yang et al studied spray autoignition characteristics under different injection pressures and cold start strategies for compression ignition engines. 7 Park et al studied the influence of temperature on the physical properties of the fuel, such as density, dynamic viscosity, and kinematic viscosity. 8 The influence of fuel temperature change on fuel properties is described when the injector temperature and fuel pipe temperature change from 0°C to 70°C.…”
Section: Introductionmentioning
confidence: 99%
“…Higher viscosity will slow down the spraying speed, breaking speed, and evaporation speed of the fuel spray 6 . Yang et al studied spray autoignition characteristics under different injection pressures and cold start strategies for compression ignition engines 7 . Park et al studied the influence of temperature on the physical properties of the fuel, such as density, dynamic viscosity, and kinematic viscosity 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in such operating conditions, it takes a longer time for the spray to overcome the barriers of the chemical reactions leading to a longer chemical delay. 19 Thus, it is extremely challenging to optimize the injection parameters to ensure an acceptable cold-start behavior with the LCR approach. Several measures like intake air heating, use of a glow plug, increase in cranking speed, multiple pilot injections, optimization of injection pressure, spray targeting, etc.…”
Section: Introductionmentioning
confidence: 99%